Pengaruh Tanggung Jawab Sosial dan Lingkungan terhadap Penghindaran Pajak - Wibawa, Marcella Mega; Setia, Angeline; Marsetio, Nany Chandra (Universitas Prasetiya Mulya, 2024)
This research aims to determine whether or not there is an impact of social and environmental responsibility costs on corporate tax avoidance in companies listed on the IDX from 2020 to 2023. Considering the widespread disclosure of CSR accompanied by news related to tax avoidance in Indonesia, that makes this topic interesting to be researched. This research uses quantitative data with cross section and time series data. The data taken are companies registered on the IDX from 2020 to 2023 from all industries except the financial industry which specifically discloses overall CSR costs, resulting in a total of 136 companies. The results of the research state that CSR costs negatively affect tax avoidance with the BTD proxy as seen from the significance results of the regression tests carried out. The small number of companies that disclose CSR costs and the short research time are the limitations in this research. Overall, it is hoped that this research will provide benefits for company management, regulators or government, academics and researchers themselves.